Modelo de gestión de emprendimiento para el desarrollo del turismo rural en la zona centro de Manabí. - Chávez Campuzano, Francisca M. (2018)
The main objective of the research was to design an entrepreneurial management model for the development of rural tourism in the central area of Manabí, which is descriptive-exploratory in nature. To carry out the proposed project, three specific objectives were planted: The first was addressed to the diagnosis of management in rural enterprises, using a characterization sheet to know the current condition of the study area both in terms of population and infrastructure and basic services , besides carrying out a SWOT analysis and the inventory of natural and cultural resources, several problems were identified as a limited tourist infrastructure, as well as a deficient touristic planning in the management of the undertakings, since there is no joint work between the public and private sectors. The second objective focused on the analysis of rural tourism potential through the application of the potentialities matrix, which allowed to identify that there is a lot of potential that is not being managed in the right way. The third objective focused on the structuring of the management model detailing, the mission, vision, strategies, objectives and activities that must be carried out to make effective the management within the rural tourism area, which will be evaluated and controlled by each of the actors, for the improvement in the management of rural enterprises in the central area of Manabí.